Effect of Culinary-Medicinal Lion's Mane Mushroom, Hericium erinaceus (Bull.: Fr.) Pers. (Aphyllophoromycetideae), on Ethanol-induced gastric ulcers in rats - Abdulla, M.A.; Ali, Hapipah Mohd; Wong, K.H.; Abdullah, N.; Sabaratnam, V.; Noor, S.M. (2008)
The cytoprotective effect of Hericium erinaceus freeze-dried fruiting bodies was investigated against ethanol-induced gastric mucosal injury in rats. Four groups of adult male Sprague Dawley rats were pretreated with distilled water (negative control), 250 mg kg(-1) H. erinaceus, 500 mg kg(-1) H. erinaceus, and omeprazole (positive control), respectively, before oral induction with absolute ethanol to generate gastric mucosal injury. Overall, rats pretreated with only distilled water suffered extensive hemorrhagic gastric mucosa lesions, whereas pretreatment with H. erinaceus or omeprazole reduced ulceration, with better cytoprotection observed in rats pretreated with omeprazole or 500 mg kg(-1) H. erinaceus compared to rats pretreated with 250 mg kg(-1) H. erinaceus. Histologically, marked damage was observed in the gastric mucosa, with submucosal edema and leucocyte infiltration in negative-control rats, whereas H. erinaceus-pretreated and positive-control rats had less gastric mucosal damage, decreased edema, and no submucosal leucocyte infiltration. In conclusion, H. erinaceus provided cytoprotection against ethanol-induced gastric ulcers in rats.